Morbidities and its Immediate Outcome in Newborns Born Through Mothers with Gestational Diabetes Mellitus (Nepal Journal of Health Sciences, 2022)
Introduction: Gestational Diabetes mellitus is associated with a significant risk of maternal and neonatal morbidity.Objective: The objective of this study was to assess the different morbidities and their immediate outcome in newborns born to mother with gestational diabetes mellitus.Methods: A descriptive cross-sectional study was done among 349 inborn neonates born to mothers with gestational diabetes mellitus, at the Department of Pediatrics and Adolescent Medicine, B.P. Koirala Institute of Health Sciences. The informed written consent and ethical approval were taken. The different socio-demographic & clinical parameters of the mothers and neonates were taken. The data was analyzed using relevant statistical tests.Results: Out of the total 11977 deliveries, there were 431 (3.6%) deliveries of mothers with gestational diabetes mellitus. More than half of the neonates were male. The mean birth weight and gestational age of the neonates were 39±2 weeks and 3100 ± 570 gram respectively. Sixty-four (18.3%) neonates had some form of morbidity. The three major morbidities in the neonates were small for gestational age (n=39, 11.2%), preterm birth (n=34, 9.7%) and neonatal hyperbilirubinemia (n=24, 6.9%). The incidence of macrosomia, hypoglycemia, hypocalcemia, polycythemia, cardiac defects, and gross congenital anomalies were 21 (6%), 22 (6.3%), six (1.7%), one (0.3%), eight (2.3%) and two (0.6%) respectively. Similarly, 22 (6%) neonates needed admission, out of which 16 (4.6%) recovered and got discharged, while six (1.4%) expired.Conclusions: The major morbidities associated with neonates born to mothers with gestational diabetes mellitus were small for gestational age, prematurity, neonatal hyperbilirubinemia, and hypoglycemia.